Microbiological and physicochemical quality and flavor of hen eggs produced under grazing or conventional systems - Guier-Serrano, Marie (2021)
Introduction. The hen egg (Gallus gallus domesticus) is a nutritious food in the diet of millions of people. Its worldwide production is obtained from conventional caging systems although alternative grazing systems are also used. Objective. To compare the microbiological and physicochemical quality and flavor of eggs produced under conventional or alternative grazing systems in Costa Rica. Materials and methods. This research was performed in Alajuela, Costa Rica, from October 2016 to May 2017. Environmental surfaces and eggs of Isa Brown hens were sampled on farms from both systems and total coliform, Escherichia coli, yeast and molds counts and absence/presence of Salmonella sp. were determined. Also, physicochemical parameters (Haugh units, yolk index, pH, yolk color, and shell hardness) were measured and a discrimination sensory test with consumers was performed. Results. The grazing production system had surfaces in contact with the eggs with total coliform and E. coli counts significantly higher than those determined for the surfaces of the conventional system. Eggs from grazing hens had total coliform counts (3,2 log10 UFC egg-1) significantly higher than conventional eggs (2,3 log10 UFC egg-1). Salmonella sp. was present in 8 % of the grazing eggs samples (incidence not significantly different from 0) and absent in the conventional eggs. A difference was found for the color of the yolk, (darker in conventional eggs). Also, there was a significant difference in the taste of both types of eggs. Conclusion. In general, microbiological and physicochemical quality and flavor of eggs produced under grazing system was different from the ones produced conventionally.